A new species of Thoracophelia (Annelida, Opheliidae) from the Yellow Sea of South Korea - Ha-Eun Lee; Geon Hyeok Lee; Gi-Sik Min (Biodiversity Data Journal, 2024)
Thoracophelia Ehlers, 1897 is a genus of Opheliidae characterised by the body divided into three distinct regions, modified parapodia in chaetiger 10 and a ventral groove restricted to the posterior half of the body. To date, 18 species have been described in the genus. Amongst them, six species have been recorded in northeast Asia.A new species, Thoracophelia foliformis sp. nov., was discovered in the intertidal zone of the Yellow Sea, South Korea. This is the first Thoracophelia species report from the Yellow Sea. This new species is closely related to T. dillonensis (Hartman, 1938) from California and T. ezoensis Okuda, 1936 from Japan in having pectinate branchiae. However, the new species can be distinguished from the two species by the unique combination of the following characteristics: 15 pairs of wrinkled pectinate branchiae with 12–15 filaments at best development and a foliaceous mid-ventral plate in the pygidium instead of one or two thick ventral cirri. Detailed descriptions and illustrations of T. foliformis sp. nov. are provided. Sequences of the mitochondrial cytochrome c oxidase subunit I (COI), nuclear 18S ribosomal DNA (rDNA) and 28S rDNA of the new species were determined and analysed.